Triple Roles of Appalachian Farm Women: Household, Farm and Wage-Earning - Penny L. Burge (Journal of Research in Rural Education, 1983)
This article describes the home, farm, and wage-earning roles of a sample of farm women who appear to be successful in managing their roles and contributing to their families. Role descriptions are based on indepth personal interviews and include measures of attitudes toward married women and work, self concept, and family decision-making structures. Implications are discussed as they relate to educational opportunities.